Acral melanoma: a retrospective cohort from the Brazilian National Cancer Institute (INCA). Issue 5 (October 2018) - Nunes, Luiz F.; Quintella Mendes, Gélcio L.; Koifman, Rosalina J.
Abstract : Acral melanoma (AM) is a rare subtype of melanoma arising on the palms, soles and subungual areas. In the Brazilian and Latin American populations, the sociodemographic and clinical-pathologic features of AM are unclear. AM tends to be more advanced at presentation because of delayed diagnoses, with poor survival. This study reports on a retrospective AM cohort from the Brazilian National Cancer Institute. We reviewed a database of 529 patients presenting with AM from 1997 to 2014 and analysed the sociodemographic and clinical-pathologic features of AM associated with overall survival and relapse-free survival. All patients were Brazilian, ranging in age from 19 to 101 years (mean 65.4; median 67.0). Two hundred and ninety-four (55.8%) patients were women. The Breslow primary lesion thicknesses ranged from 0.0 to 65.0 mm (mean 8.3 mm; median 5.0 mm). Of these patients, 43.3% had the acral lentiginous histologic subtype. Plantar was the most frequently involved site (68.5%), and ulcers and mitosis were present in 79.0 and 86.4% of these cases, respectively. Multivariate analysis results found that Breslow thickness of 1.03 (95% confidence interval: 1.01–1.05; P =0.01) and ulceration of 2.70 (95% confidence interval: 1.00–7.06; P =0.05) were poor prognostic indicators of overall survival. AM tumours were thick on diagnostic tests and were associated with poorer survival outcomes. Unfavourable prognosis likely derives from the delayed diagnosis compared with other melanoma subtypes.